The future of the thermohaline circulation - a perspective - Stocker, Thomas F.; Knutti, Reto; Plattner, Gian-Kasper (American Geophysical Union, 2001)
Evidence from paleoclimatic archives suggests that the ocean atmosphere system has undergone dramatic and abrupt changes with widespread consequences in the past. Climatic changes are most pronounced in the North Atlantic region where annual mean temperature can change by 10° C and more within a few decades. Climate models are capable of simulating some features of abrupt climate change. These same models also indicate that changes of this type may be triggered by global warming. Here we summarize what is known about such future changes and discuss the state of our knowledge about these potential threats to the stability of the Earth System.